#### Answer

43

#### Work Step by Step

Plugging in the given value of d and using order of operations to solve:
$$ = (6+1)^2 -6 \\ = 7^2 -6 \\ =49-6 \\=43$$

Chegg costs money, GradeSaver solutions are free!

Published by
McDougal Littell

ISBN 10:
0618595414

ISBN 13:
978-0-61859-541-9

43

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.